Analisis Pengendalian Persediaan Menggunakan Metode Probabilistik dengan Kebijakan Backorder dan Lost sales - Fatma, Erika; Pulungan, Dian Serena (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
High fluctuating demand at companies encourages to perform inventory control. This study aims to determine the exact inventory control method for the company, which minimizes the inventory cost and inventory amount provided by the company. This research analyzes various aspects related to the system and inventory cost used by the company. This research uses probabilistic inventory methods, which are probabilistic controls, P models, and Q models. Based on data processing, P model provides an optimal solution. P system provides cost and amount of optimal safety stock compared to other inventory models.